Wideband MIMO antenna for SCADA Wireless Communication Backhaul Application (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A wideband multiple-input-multiple-output (MIMO) antenna system with common elements suitable for SCADA wireless communication backhaul application which is operating frequency of 0.85-2.6GHz that can cover global system for mobile communication (GSM) 900MHz and 1.8GHz, The Universal Mobile Telecommunication System (UMTS) 2GHz, Wi-Fi (2.4GHz) and Long Term Evolution (LTE) 2.6GHz is proposed. The proposed MIMO antenna system consists of four microstrip feedline with common radiating element and a frame shaped ground plane. A single port antenna also was designed and presented in this paper to show the process to design wideband MIMO antenna structure. The radiator of the MIMO antenna system is designed as the shape of modified rectangle with straight line at each corner to enhance the bandwidth frequency. To improve the isolation between ports, the ground plane is modified by inserting four L-slots in each corner to reduce mutual coupling. For an antenna efficiency of more than 60%, the simulated reflection coefficients are below -10dB for all ports at expected frequency. Simulated isolation is achieved greater than -10dB by using a modified ground plane. Also, a low envelope correlation coefficient (ECC) less than 0.1 and polarization diversity gain of about 10dB with the orthogonal mode of linear polarization and omnidirectional pattern during the analysis of the radiation characteristic are achieved. Therefore, the proposed design can be used for SCADA wireless communication backhaul application.